Conventional farming reduces the activity of earthworms: Assessment of genotoxicity test of soil and vermicast - Singh, Jaswinder; Singh, Sharanpreet; Vig, Adarsh Pal; Bhat, Sartaj Ahmad; Hundal, Swarndeep Singh; Yin, Rui; Schädler, Martin (Agriculture and Natural Resources, 2018)
The activity of earthworms in an agricultural field and botanical garden was substantiated. Samples of vermicast produced by earthworms along with the soil were collected from an agricultural field (conventional farm) and a botanical garden and their genotoxic assessment were observed on the root tips cells of Allium cepa. The mitotic index (MI) was increased in both vermicast samples compared to soil. However, the mean (±SE) MI was greater in the vermicast (13.93 ± 0.67) collected from the botanical garden compared to the agricultural vermicast (11.40 ± 0.51). Chromosomal aberration levels were greater in the soil of the agricultural field (14.88%) compared to soil from the botanical garden (9.11%), whereas a reduction in chromosomal aberrations was observed in the vermicast of both sites. The number of earthworms was less on the conventional farm (18 earthworms/1800 cm2 area) compared to the botanical garden (72 earthworms/1800 cm2 area). Thus, this study showed that the activity of earthworms was less in an agricultural field where there may have been more application of chemical fertilizers and pesticides compared to a site using more organic manure with reduced genotoxicity.